Identification on the Need of English Public Speaking Class for Students at the Tourism Destination Study Program - Milawaty Milawaty; Mutika Andadari; Vemas Aditya; Lely Dian Utami (Journal of Language, Communication, and Tourism, 2023)
This study aims to identify the need of English public speaking skill for students at the Tourism Destination Study Program and formulate the required solution. This study was motivated by recent student events called “Seminar Pariwisata” or Tourism Seminar where all the students had to present their projects from the Integrated Field Practicum and also “Duta Polije”, a contest where campus ambassadors were selected. This study was an aftermath evaluation following the conducted events with the hope to bring an improvement in the future for both the students and the study program. This was a descriptive-qualitative study and the data were collected through observation, documentation and interview. The results of the study show that there is a need in providing students with English public speaking skill through intensive public speaking classes, to support them especially in non-academic activities. This is also useful to equip them with additional competencies in order to help them in the workplace after graduation, especially to have a career in the tourism business. The class can be conducted during the running academic year by integrating the class with English courses, by adding the public speaking class at the speaking skill section of the RPS (Semester Teaching Plan) and BKPM (Student’s Workbook) of English courses. This idea is suggested to be taken into consideration to create a better educational supports for the students as well as for the development of the study program in the future.